2015
DOI: 10.1038/ki.2015.237
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral natural killer cell and allo-stimulated T-cell function in kidney transplant recipients associate with cancer risk and immunosuppression-related complications

Abstract: Reducing immunosuppression has been proposed as a means of preventing cancer in kidney transplant recipients but this can precipitate graft rejection. Here we tested whether anti-tumor natural killer (NK) cell and allo-responsive T-cell function in kidney transplant recipients may predict cancer risk and define risk of rejection. NK cell function was measured by the release of lactate dehydrogenase and T cell allo-response by interferon-γ quantification using a panel of reactive T cell Enzyme-Linked ImmunoSpot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…PPV and NPV depend on prevalence of the disease in the studied population. Considering that the proportion of OIS patients in this cohort (33%, 24 of 71) is encountered also in real-life settings, 20 present PPV and NPV values are not biased by an unexpected frequency of the event. In this respect, the validated NPV is at a level similar to what led previous diagnostic tests, such as B-type natriuretic peptide, to be translated into clinical practice 21 .…”
Section: Discussionmentioning
confidence: 85%
“…PPV and NPV depend on prevalence of the disease in the studied population. Considering that the proportion of OIS patients in this cohort (33%, 24 of 71) is encountered also in real-life settings, 20 present PPV and NPV values are not biased by an unexpected frequency of the event. In this respect, the validated NPV is at a level similar to what led previous diagnostic tests, such as B-type natriuretic peptide, to be translated into clinical practice 21 .…”
Section: Discussionmentioning
confidence: 85%
“…NK cells play a critical role in suppressing cSCC development in murine models [39], though the TME may modulate their cytotoxicity through downregulation of activating receptors [53]. Genetic or acquired impaired function or reduced number of NK cells is associated with increased risk of herpesvirus, papillomavirus, and cSCC in humans [54,55,56,57]. This indicates that NK cells play a key role in immunosurveillance against cSCC development.…”
Section: The Role Of Innate Immunitymentioning
confidence: 99%
“…Hope et al[ 83 ] in their study of 82 KTRs (56 with known malignancy, 26 without) found that weak NK cell activity, derived from lactate dehydrogenase and interferon-gamma quantification using reactive T-cell enzyme-linked immunospot, was associated with metastatic cancer, cancer-related death, or septic death [HR = 2.1 (95%CI: 0.97 to 5.00)][ 83 ].…”
Section: Novel Biomarker Classificationmentioning
confidence: 99%